Pengaruh Kualitas Layanan, Kualitas Produk, Dengan Kepercayaan Sebagai Variabel Moderasi Terhadap Kepuasan Nasabah - Nuri Annisa Fitri; Hisbullah Basri; Memen Lewispri (FORBISWIRA FORUM BISNIS DAN KEWIRAUSAHAAN, 2023)
This study aims to determine the effect of service quality, product quality, with trust as a moderating variableon customer satisfaction. Respondents in this study were customers at PT. Bank Syariah Indonesia (Persero) Tbk.Palembang Branch. This study uses two testing methods, namely simple regression analysis and Moderated RegressionAnalysis (MRA). The first hypothesis, Service Quality has a positive and significant effect on Customer Satisfaction.The calculated F value is 88,528 with a Sig value. = 0.000 < 0.05. The linearity standard is met. The secondhypothesis, Product Quality has a positive and significant effect on Customer Satisfaction. The calculated F value is93,683 with a Sig value. = 0.000 < 0.05. The linearity standard is met. The third hypothesis, the RSquare value in the firstregression equation is 0.475 or 47.5%. The second regression equation after the moderating variable (Trust), theRSquare value increased to 0.552 or 55.2%. In conclusion, the Trust variable can strengthen the influence of theService Quality variable on the Customer Satisfaction variable. The fourth hypothesis, the RSquare value in the firstregression equation is 0.489 or 48.9%. The second regression equation after the moderating variable (Trust), theRSquare value increased to 0.593 or 59.3%. In conclusion, the Trust variable can strengthen the influence of theProduct Quality variable on the Customer Satisfaction variable.